Psychophysical evaluation of auditory signals in passenger vehicles. (March 2017) - Chi, Chia-Fen; Dewi, Ratna Sari; Huang, Min-Hua
Abstract: Twenty-one experienced drivers were recruited for the evaluation of sounds of four functions (horn, indicator, door open warning, and parking sensor) made by 11 car brand names. Each participant was required to evaluate all of the above sound signals by a pair-comparison test. After the comparison test, each participant was shown his/her pair-comparison result and was asked to comment on their preference and appropriateness of a sound. The physical properties and interview data were compared and summarized to propose design recommendations. Our results indicate that complex tones and a fundamental frequency between 500 and 1000 Hz were most preferred for horns while for indicators the preferred sounds had a higher dominant frequency. To reduce monotony, the indicators with double clicks and an OFF time interval of between 330 and 400 ms between two clicks were most preferred. Regarding door warning sounds, the waveform starting with a higher intensity then fading towards zero intensity is most preferred while for parking sensors, sounds beginning with a longer OFF time (about 500 ms) and having 3 or 4 distinctive tempo variations were most preferred. The relationship between pleasurability and pitch, loudness, and the tempo of sound signals basically followed an inverted-U function. Sound designers should avoid using very extreme parameter values when generating sound for a given function. Highlights: In-vehicle auditory signals were evaluated with a subjective evaluation test. Paired-comparison result, physical attributes and interview comments were compared. Complex tones and less monotonous sounds were recommended. Avoid using very extreme parameter values when generating sound.